Association of Pregnancy History and Cervical Cancer Screening in a Community Sample of Sexual Minority Women - Greene, Madelyne Z. (J Womens Health (Larchmt), 2019)
Background: Sexual minority women (SMW) face barriers to healthcare that may result in lower utilization of cervical cancer screening. Previous experiences with the healthcare system—specifically reproductive health-related encounters—have the potential to affect future use of screening services. This study aimed to examine the association between pregnancy history and cervical cancer screening in a diverse sample of SMW. Anderson's Behavioral Model of Health Services Use guided the selection of variables included in the study. Methods: We performed a secondary analysis of cross-sectional data from the third wave of the Chicago Health and Life Experiences of Women (CHLEW) Study, a longitudinal study of SMW in the Midwestern United States. We performed multivariable logistic regression to address the study aims, restricting the sample to women ages 21–45 (n = 430). Results: Reporting a previous pregnancy was consistently positively associated with past-year Pap testing. In the multivariable model, bisexual identity and disclosing one's sexual orientation to healthcare providers were also positively associated with past-year Pap test. Conclusions: This analysis provides preliminary evidence that SMW who have been pregnant are more likely to receive Pap testing and that multiple sociodemographic factors are likely to impact screening in this population. Clinicians should screen all patients with a cervix for cervical cancer and should encourage screening for all SMW. Future studies should prioritize longitudinal analyses to examine the temporality of reproductive history and healthcare seeking, focus on where SMW seek care, and understand how intersecting components of identity may shape the healthcare utilization of this population.